Desmoplastic Small Round Cell Tumor of the Ovary: A Case Report with a New Modality of Treatment and Review of the Literature - Vujić, Goran; Mikuš, Mislav; Matak, Luka; Bonevski, Aleksandra; Babić, Ivan; Planinić, Pavao; Babić, Damir; Ćorušić, Ante (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2020)
Objective Desmoplastic small round cell tumor (DSRCT) is a rare intraabdominal neoplasm that grows along serosal surfaces and is primarily found in young men. To date, only 16 cases of ovarian DSRCT have been previously reported in women in the English literature, and no large population-based studies on this topic exist.Case Report We report the case of a 19-year-old virgo with unremarkable past medical history, initially presented with abdominal fullness. After being treated with the optimal treatment modality (primary and secondary surgical debulking, unique chemotherapy, protocol and adjuvant radiotherapy), the patient has remained without tumor disease for 40 months.Conclusion Although the best therapy for patients with DSRCT has yet to be determined, combining complete surgical resection, adjuvant chemotherapy, and radiotherapy is required to prolong survival and to achieve proper quality of life.
Keywords: desmoplastic small round cell tumor; ovary; surgical debulking; adjuvant chemotherapy; radiotherapy; immunohistochemistry